Why Is the AfD so Successful in Eastern Germany? An Analysis of the Ideational Foundations of the AfD Vote in the 2017 Federal Election - Maria Pesthy; Matthias Mader; Harald Schoen (Politische Vierteljahresschrift, 2020)
The Alternative for Germany party (AfD) has been more successful electorally in eastern than in western Germany. In this paper, we look at nativism coupled with populist attitudes as possible contributors to the 2017 federal electoral outcome. We compare two alternative mechanisms for the varying election results, the first being whether individuals living in eastern Germany are, on average, more nativist and populist inclined; the second, whether nativism and populism are more salient when these voters go to the polls. The results show that there indeed exists a~slightly higher level of nativist and populist sentiment among the east German citizens than among the west Germans. This difference concerns older east Germans in particular, who were politically socialised during the German separation. Furthermore, elements of nativist and populist ideas explain electoral support for the AfD in both parts of the country, but nativism appears to be more relevant in the east. Overall, the analysis of the short-term campaign panel data from the German Longitudinal Election Study suggests that the inspected ideational foundations contribute to the east–west gap in AfD support without accounting for it completely.
Keywords: 320; AfD vote; Populism; Nativism; East–west differences; AfD-Wahl; Populismus; Nativismus; Ost–West-Unterschiede